2015
DOI: 10.1111/acel.12341
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐stimulated interleukin‐15 is controlled byAMPKand regulates skin metabolism and aging

Abstract: Aging is commonly associated with a structural deterioration of skin that compromises its barrier function, healing, and susceptibility to disease. Several lines of evidence show that these changes are driven largely by impaired tissue mitochondrial metabolism. While exercise is associated with numerous health benefits, there is no evidence that it affects skin tissue or that endocrine muscle-to-skin signaling occurs. We demonstrate that endurance exercise attenuates age-associated changes to skin in humans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
140
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 45 publications
0
140
1
2
Order By: Relevance
“…These findings make sense since skin and bone tissue are both primarily made up of collagen type I [9, 10]. Furthermore, Crane et al [11] showed that endurance exercise training in elderly sedentary subjects increased reticular dermis collagen content. From a range of publications it is also known that the nutritional status plays an important role in the maintenance of healthy skin [12-22].…”
Section: Discussionmentioning
confidence: 99%
“…These findings make sense since skin and bone tissue are both primarily made up of collagen type I [9, 10]. Furthermore, Crane et al [11] showed that endurance exercise training in elderly sedentary subjects increased reticular dermis collagen content. From a range of publications it is also known that the nutritional status plays an important role in the maintenance of healthy skin [12-22].…”
Section: Discussionmentioning
confidence: 99%
“…IL15 and IL15RA levels are elevated acutely during low-grade inflammation induced by exercise[812], but also chronically in pathological conditions such as rheumatoid arthritis, particularly in the synovial fluid[7]. IL15 SNPs correlate with bone mineral density and cortical bone volume in humans[17,45].…”
Section: Discussionmentioning
confidence: 99%
“…IL15 is a widely expressed pro-inflammatory cytokine and also functions as a myokine that is secreted from muscle in response to exercise[812]. Elevated IL15 receptor alpha (IL15RA) levels are found in the synovial fluid of patients affected by rheumatoid arthritis and other chronic inflammatory diseases that are associated with bone loss[7,13].…”
Section: Introductionmentioning
confidence: 99%
“…Crane and colleagues demonstrated that exercise attenuated skin changes associated with aging in both humans and mice [49]. Physical activity induces IL15 release from skeletal muscles through the AMPK pathway[49] and IL15 modulates mitochondrial function in skin. Interestingly, IL15 injections into mice mimic anti-aging effects of exercise both in muscle and skin.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, IL15 injections into mice mimic anti-aging effects of exercise both in muscle and skin. Overall, this pioneering study describes a mechanism that explains, at the molecular level, how physical activity attenuates skin aging through IL15-dependent processes[49]. …”
Section: Introductionmentioning
confidence: 99%